Cloud security: an upcoming development in hybrid automated storage protection systems - Srividya Bharadwaja VenkataSubbu; Smitha Sasi; Meharunnisa Sakkar Sab Pakeer Saheb; Harikeerthan Mysore Keshava Rao; Soumya Seetharamaiah (Bulletin of Electrical Engineering and Informatics, 2026)
The need for cloud storage is growing daily, despite its apparent reliability and scalability. Because of the complexity of data security, including privacy and confidentiality, it is difficult to store and manage user data remotely. An untrustworthy insider could be the cloud third party responsible for managing the data security issues occurring within the cloud services. An automated hybrid cryptographic algorithm for cloud data storage is provided by the current research to improve data protection and guarantee information confidentiality without any disruption from cloud third parties. Two encryption methods that are employed to attain high performance and efficiency are enhanced automated concurrent encryption for data blocks (CEDB) and improved automated asynchronous encryption for data streams (AEDS). By converting the fixed S-box in the traditional AES to a modifying S-box using a ternary Galois field (GF) and complementary ternary GF, we present a novel encryption technique in enhanced automated concurrent encryption. Furthermore, the matrix utilized for the AES mix column approach is converted into a dynamic matrix using the ternary GF and complementary ternary GF. This cryptographic approach aims at providing cloud data security, ensuring confidentiality, and integrity for the user’s information even in compromised situations.